SΦ-supplemented subgroups of finite groups - Xianhua Li; Tao Zhao (Український математичний журнал, 2012)
We call H an SΦ-supplemented subgroup of a finite group G if there exists a subnormal subgroup T of G such that G = HT and H ∩ T ≤ Φ(H), where Φ(H) is the Frattini subgroup of H. In this paper, we characterize the p-nilpotency and supersolubility of a finite group G under the assumption that every subgroup of a Sylow p-subgroup of G with given order is SΦ-supplemented in G: Some results about formations are also obtained. Пiдгрупу H називають SΦ-доповнюваною пiдгрупою скiнченної групи G, якщо iснує така субнормальна пiдгрупа T групи G, що G=HT and H⋂T≤Φ(H), де Φ(Н) є пiдгрупою Фраттiнi пiдгрупи H. У цiй статтi охарактеризовано p-нiльпотентнiсть та надрозв’язнiсть скiнченної групи G за припущення, що кожна пiдгрупа силовської p-пiдгрупи групи G заданого порядку є SΦ-доповнюваною в G. Отримано також деякi результати щодо формацiй.